Interview with a Sironko farmer - Mr. Wogobi George - Margiotta, S. (International Institute of Tropical Agriculture, 2019)
Interviews with a farmers from Sironko discussing his experience of working with IITA and Olam and engaging in the Stepwise Sironko demonstration plot pilots.